The Influence of Road Infrastructure Access on The Socio-Economic Life of The Community in Kertanegla Village, Bojonggambir District, Tasikmalaya - Kheysa Dwinanda Agustina; Ulfa Yulianti; Siti Samroh Qiadiah; Siti Fadjarajani (International Journal of Geography, Social, and Multicultural Education, 2023)
Access to infrastructure plays a very important role in improving the social and economic life of rural communities. Good and affordable infrastructure can facilitate economic activity, increase accessibility, and strengthen connectivity between regions. This research aims to relate the influence of road infrastructure access on the socio-economic life of the community in Kertanegla Village, Bojonggambir District, Tasikmalaya Regency. In this research, the research method used is a descriptive quantitative method with linear regression analysis techniques. The results obtained from this research are that the construction of road infrastructure on economic growth in Kertanegla Village has an influence but is not significant